Perancangan Bot Pada Discord Untuk Pembacaan Sensor Di Raspberry Pi Dengan Sistem Learning Yang Dinamis - Rizki Septiansyah; Sabriansyah Rizqika Akbar; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
On this research, author will design a bot that will run on raspberry pi and can be used to read sensor value on raspberry pi by using dynamic learning system.On its usage this bot will run on social media that named Discord and user can give some commands on server chatbox so bot can running. On implementation, this bot already been tested its function and every case that tested can work properly and declared successful.On accuracy test, obtained average error pecentage with LM35 sensor 0.541% and on HY-SRF05 sensor 3.387%. Average execution time test with temperature sensor LM35 on learn command 545.54ms, cmd command 8.007ms and forgot command 1.07ms. Average execution time test with ultrasonic sensor HY-SRF05 on learn command are 661.65ms, cmd command 5.42ms and forgot command 1.24ms. Average execution time test with LDR sensor on learn command are 646.20ms, cmd command 5.43ms and forgot command 1.31ms.